Crohn’s disease, irritable bowel syndrome, and chronic fatigue: the importance of communication and symptom management—a case report - Johannes Haedrich; Roman Huber (Journal of Medical Case Reports)
Abstract Background Crohn’s disease and irritable bowel syndrome may both cause abdominal pain and diarrhea. Irritable bowel syndrome not only is an important differential diagnosis for Crohn’s disease but also occurs in one out of three patients with Crohn’s disease in remission in parallel. If not adequately diagnosed and treated, additional functional symptoms such as fatigue and/or muscle pain may develop, indicating a more severe course. Case presentation A 64-year-old Caucasian male with long-standing, widely inactive Crohn’s disease presented with persistent diarrhea, bloating, abdominal pain, general fatigue, unexplained hip pain, and frequent shivering with cold extremities, which had worsened following a gastrointestinal infection and psychological stress. A plausible explanation of his symptoms, based on an understanding of mind–body interactions, the autonomic nervous system, and temperature regulation, combined with symptom relief, was associated with rapid and sustainable improvement. After 2.5 years of follow-up, the patient is almost symptom-free. Conclusions This case report exemplifies the interrelation between organic (Crohn’s disease) and functional diseases (irritable bowel syndrome, chronic fatigue syndrome, and somatoform pain). It further demonstrates that these connections may be overlooked in daily practice and that providing a plausible explanation in combination with symptom relief may be important for patients with functional syndromes.